Investigation of the Pattern of the Effect of Age Group, Time, Period, and Birth Cohort on the Incidence of Suicidal Deaths in Lorestan Povince, 2006-2015 - S Ebrahimi Kebria; SS Hashemi Nazari; Y Mdehrabi; B Nazparvar; A Shojaei; SD Mirtorabi (مجله اپیدمیولوژی ایران, 2019)
Background and Objectives: Suicide is one of the psychosocial problems in Lorestan Province due to its socio-cultural and economic structure. The aim of this study was to investigate the effect of age group, time period, and birth cohort on the suicide incidence in Lorestan Province during the 2006-2015.